Genetic Studies On The GHSR and IGF1R and Their Relationship With Stunting: A Systematic Literature Review - Saarah Hamidah Asmara Indratno; Jekmal Malau; Ahsanal Kasasiah (Universitas Labuhanbatu, 2024)
Stunting, also known as short stature, is a condition that occurs in children where children grow too short for their age. It can be influenced by several external and internal factors. This study explored various databases including Pubmed, Science Direct, Sage Journal, Springer Link, with keywords: